Hubungan Body Image terhadap Self Efficacy Pasien Kanker Payudara - Lita Eka Putri Ngarani; Dwi Fitriyanti; Anna Jumatul Laely (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Breast cancer is a type of cancer that affects the breast organs and is characterized by abnormal cell growth and development. The treatment for breast cancer can impact both the physical and psychological conditions of patients. One of the physical impact is body image, while the psychological impact includes the emergence of negative feelings that can affect breast cancer patients’ self-efficacy. This study aims to determine the relationship between body image and self-efficacy in breast cancer patients. The study was conducted at Dr. Kariadi Central Public Hospital Semarang, with a sample size of 63 respondents. The sampling technique used was purposive sampling, where subjects were selected based on inclusion criteria set by the researcher. The instruments used in this research were the Body Image Scale and the General Self-Efficacy Scale. This study employs quantitative methods with a cross-sectional research design. Based on the Spearman rank statistical test, the p-value was 0.000 (<0.05), indicating that Ha is accepted, and Ho is rejected. This shows that there is a significant correlation between body image and self-efficacy in breast cancer patients at Dr. Kariadi Central Public Hospital Semarang. It is hoped that the recommendations from the research results can enhance nursing knowledge related to body image and self-efficacy in breast cancer patients.